Dal'nii Vostok . Dal'nii Vostok . The Far East . Дальний Восток - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Boris Yeltsin's visit to Magadan prior to the referendum; Shokhin's and Alexander Baburin's visit to the Khabarovsk region; public opinion of the political situation in Russia prior to the referendum. Featured in the program: Yeltsin, Boris Nikolayevich (President of the Russian Federation); Baburin, Sergei Nikolaevich (Politician); Shokhin, Aleksandr (Vice Chairman of the Government of the Russian Federation) Series description: The program consists of regional television reports of the Dal'nevostochnogo federal'nogo okrug [Far Eastern Federal District] of the Russian Federation. Визит Бориса Ельцина в Магадан перед референдумом; визит Александра Шохина и Александра Бабурина в Хабаровский край; общественное мнение о политической ситуации в России перед референдумом. В программе участвуют: Ельцин, Борис Николаевич (Президент Российской Федерации); Бабурин, Сергей Николаевич (Политик); Шохин, Александр (Заместитель председателя Совета правительства Российской Федерации) Описание серии: Программа состоит из репортажей регионального телевидения Дальневосточного федерального округа Росчсийской Федерации.